Online partial discharge counting system using microcontroller PIC 16F877A and FPGA technology - Emilliano; Chakrabarty C.K.; Ghani A.B.A.; Ramasamy A.K. (2023)
This paper is purely a design circuit to implement Partial Discharge (PD) detection in FPGA technology using Xilinx ML405 board (Virtex 4) and real time ADC in microcontroller PIC 16F877 A. The research involve ISE Simulator version 10.1i (Xilinx) and ISE Xilinx Synthesized Technology (XST) using Very high integrated circuit Hardware Description Language (VHDL) programming to evaluate the use of Field Programming Gate Array (FPGA) for the detection and counting of partial discharge signals in high voltage underground cable. The research also involve PCWH CCS C Compiler using C programming to run real time ADC in microcontroller PIC 16F877A. The impulse of PD signals is simulated by impulse generator in the lab simulation. The input data (PD signals) in high voltage underground cable have very fast rise time in the range of 1 ns to 2 ns in the real system. The speed clock of the real time ADC in microcontroller PIC is 20 MHz. This paper shows analysis data of ability of real time ADC in microcontroller PIC to measurement, detect and counting PD signal using FPGA technology. The combination of all blocks of PD detection circuit system is tested by using ISE Xilinx Synthesis Technology (XST) and ISE implementation. In the next stage, this method will be implemented on a next lab simulation scale using real PD signals that is detected by 3D magnetic probe sensor in real underground cable in laboratory for testing and validation before test in the real situation. 2010 lEEE.